Alluvial Island Herbal Plant Landscape And The Ethno-Medico Malay Tradition Of Binamulia (Study Of The Bomoh Tradition-Based Medicine System In Malay Villages, Meranti Islands Regency, Riau) - Yusuf, Yusmar; Resdati, Resdati; Siti Sofro Sidiq, Rd; Riskiansyah, Muhammad (International Journal of Educational Research & Social Sciences, 2022)
This study aims to identify and analyze various types of herbal plants around the Sago forest ecosystem which are often used as traditional medicine by the people of the Meranti Islands. This study uses qualitative methods, withdata collection techniques through interviews and direct observation in the field. The result was found a lot of herbal plants around the sago ecosystem that have many benefits and extraordinary benefits. However, nowadaystraditional medicine with herbal ingredients has started to disappear dueto the development of chemical drugs andthe decreasing number of peoplewho understand and understand traditional medicine. Therefore, this is where the importance of this research is to explore and examine and introduce efficacious herbal plants so that they can be preservedThis study aims to identify and analyze various types of herbal plants around the Sagoforest ecosystem which are often used as traditional medicine by the people of the Meranti Islands. This study uses qualitative methods, with data collection techniquesthrough interviews and direct observation in the field. The result was found a lot of herbal plants around the sago ecosystem that have many benefits and extraordinary benefits. However, nowadaystraditional medicine with herbal ingredients has started to disappear due to the development of chemical drugs and the decreasing number of people who understand and understand traditional medicine. Therefore, this is where the importance of this research is to explore and examine and introduceefficacious herbal plants so that they can be preserved